Development of recombinant cells encoding surface protein of Corynebacterium pseudotuberculosis against caseous lymphadenitis in goats - Shahridon, Syafiqah Adilah; Saad, Mohd Zamri; Zakaria, Zunita; Mansor, Rozaihan (International Network for Natural Sciences, 2016)
Caseous lymhadenitis is an infectious disease caused by an intracellular bacterium, Corynebacterium pseudotuberculosis. Control is via vaccination. This report describes construction of two recombinant cells; one that carried the putative surface-anchored protein, the SpaA (pET32/LIC-SP31) and the other the glyceraldehyde-3-phosphate dehydrogenase protein, the GAPDH (pET32/LIC-SP40). The recombinant cells were introduced into goats before aAntibody response by the goats and protective capacities of the recombinant cells were measured. Fifteen goats were divided into3 groups. Group 1 was injected intramuscularly with PBS, Groups 2 and 3 were injected on days 0 and 14 with 106CFU/ml of recombinant pET32/LIC-SP31 and pET32/LIC-SP40 cells, respectively. Serum samples were collected weekly to determine the antibody levels using ELISA. Two weeks after the last vaccination, all goats were challenged subcutaneously with 109CFU/ml of live C. pseudotuberculosis. The results revealed that goats exposed to the recombinant cells showed significantly (p<0.05) higher IgG level compared to the control that lasted for 11 weeks. Generally, the exposed groups showed similar antibody pattern although those exposed to pET32/LIC-SP40 showed insignificantly (p>0.05) higher level in the first 7 weeks than the recombinant pET32/LIC-SP31. Following challenge at week 6, abscesses were observed in the lymph nodes of all groups while C. pseudotuberculosis was successfully isolated. The recombinant cells were able to induce humoral response but failed to protect the goats against challenge by live C. pseudotuberculosis.